D8 Open Data for Agriculture Presentation by Daniel Mason-D'Croz - Mason-D'Croz, Daniel (2013)
Presentation by Daniel Mason-D'Croz at the D8 Open Data for Agriculture Side event at IFPRI on May 1, 2013.